Nanomedicine for the Treatment of Viral Diseases: Smaller Solution to Bigger Problems - Suvankar Ghorai; Harshita Shand; Soumendu Patra; Kingshuk Panda; Maria J. Santiago; Md. Sohanur Rahman; Srinivasan Chinnapaiyan; Hoshang J. Unwalla (MDPI AG, 2024)
The continuous evolution of new viruses poses a danger to world health. Rampant outbreaks may advance to pandemic level, often straining financial and medical resources to breaking point. While vaccination remains the gold standard to prevent viral illnesses, these are mostly prophylactic and offer minimal assistance to those who have already developed viral illnesses. Moreover, the timeline to vaccine development and testing can be extensive, leading to a lapse in controlling the spread of viral infection during pandemics. Antiviral therapeutics can provide a temporary fix to tide over the time lag when vaccines are not available during the commencement of a disease outburst. At times, these medications can have negative side effects that outweigh the benefits, and they are not always effective against newly emerging virus strains. Several limitations with conventional antiviral therapies may be addressed by nanotechnology. By using nano delivery vehicles, for instance, the pharmacokinetic profile of antiviral medications can be significantly improved while decreasing systemic toxicity. The virucidal or virus-neutralizing qualities of other special nanomaterials can be exploited. This review focuses on the recent advancements in nanomedicine against RNA viruses, including nano-vaccines and nano-herbal therapeutics.